2014
DOI: 10.1371/journal.pone.0081850
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Running Velocity and the Energy Cost of Turning during Running

Abstract: Ball game players frequently perform changes of direction (CODs) while running; however, there has been little research on the physiological impact of CODs. In particular, the effect of running velocity on the physiological and energy demands of CODs while running has not been clearly determined. The purpose of this study was to examine the relationship between running velocity and the energy cost of a 180°COD and to quantify the energy cost of a 180°COD. Nine male university students (aged 18–22 years) partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
4
31
2
Order By: Relevance
“…The DFAM is a unique method that can measure the energy cost of an instantaneous movement performed within 1 s or over a few seconds. We have already demonstrated that the energy cost of a single change of direction during running at various velocities can be calculated using DFAM (Hatamoto et al 2013(Hatamoto et al , 2014. The present results indicate that DFAM can be applied for instantaneous movements in daily life, such as an STS movement.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The DFAM is a unique method that can measure the energy cost of an instantaneous movement performed within 1 s or over a few seconds. We have already demonstrated that the energy cost of a single change of direction during running at various velocities can be calculated using DFAM (Hatamoto et al 2013(Hatamoto et al , 2014. The present results indicate that DFAM can be applied for instantaneous movements in daily life, such as an STS movement.…”
Section: Discussionsupporting
confidence: 51%
“…Hatamoto et al examined the energy cost of a turn, which is an instantaneous movement observed frequently in ball games (Hatamoto et al 2013(Hatamoto et al , 2014. DFAM is the idea that gross EE increases linearly as movement frequency increases if the EE, which is determined for performing one movement, accumulates by conducting movements repeatedly.…”
Section: Evaluating the Energy Expenditurementioning
confidence: 99%
See 1 more Smart Citation
“…During shuttle running, the time spent accelerating increases as running speed increases (Akenhead et al, 2015). Consequently, the energy cost of turning increases with increasing running speed (Hatamoto et al, 2014;Akenhead et al, 2015). The 20mSRT is an exercise protocol in which running speed and turning frequency increase as the test progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Hatamoto et al [14] showed that turning during sports required deceleration and acceleration and thus increased one's EE. The magnitude of the increase depended on both the turn frequency and running velocity.…”
Section: Introductionmentioning
confidence: 99%